CRITICAL THINKING AND BIOLOGICAL LITERACY: RELATIONSHIP WITH CONCEPTUAL UNDERSTANDING OF PLANT TISSUE - Rizhal Hendi Ristanto; Mieke Miarsyah; Shinta Alief Fitrianingtyas (EDUSAINS, 2023)
Biology learning currently requires students to have critical thinking ability and biological literacy so that they can improve conceptual understanding. The purpose of this study was to analyze the correlation between critical thinking ability and biological literacy in conceptual understanding of plant tissue. This research method is quantitative descriptive research using a correlational study. The research sample used 92 students from SMA Negeri 37 Jakarta. critical thinking ability instrument uses essay type test with 24 questions, biological literacy uses multiple choice type test with 10 questions and concept mastery is a multiple-choice type test with 30 questions. In variable showed that the fifth indicator was the lowest in critical thinking, biological literacy was the lowest in the nominal dimension, and mastery of concepts corresponded to the difficulty of the cognitive level of the questions. The results of hypothesis testing show that there is a positive and linear correlation between critical thinking ability and biological literacy with conceptual understanding of plant tissue. Multiple linear regression model Multiple linear regression model Ŷ = 13.077 + 0.399X1 + 0.413X2. Critical thinking ability and biological literacy contribute 33.5% to conceptual understanding. Critical thinking skills and biological literacy have a positive relationship but with different strengths and levels of contribution to the mastery of plant tissue concepts.